1998
DOI: 10.1021/cm980212j
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Modeling and High-Pressure−High-Temperature Synthesis of Perovskites Containing Monovalent Silver

Abstract: The program POTATO, which was developed to model distorted perovskite structures, has been used to assess the stability of hypothetical compositions and guide the synthesis of new materials at high pressures and high temperatures. The initial result of this effort is the synthesis of two new perovskites, Ca2NdAgTi4O12 and NdAgTi2O6, which were synthesized at 14−14.5 GPa and 1000 °C using the uniaxial split sphere anvil type press (USSA-2000). Both compounds are perovskites distorted from the ideal cubic struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 44 publications
(57 reference statements)
2
26
0
Order By: Relevance
“…This distortion is a response to the fact that the sodium ion is too small for a cubic MTeO 6 2− network. Unfortunately, the presence in each case of a minor (<3 wt%) unidentified impurity phase(s), whose peaks overlapped in some instances with the perovskite reflections, did not allow for accurate determination of the oxygen positions.…”
Section: Rapid Communicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This distortion is a response to the fact that the sodium ion is too small for a cubic MTeO 6 2− network. Unfortunately, the presence in each case of a minor (<3 wt%) unidentified impurity phase(s), whose peaks overlapped in some instances with the perovskite reflections, did not allow for accurate determination of the oxygen positions.…”
Section: Rapid Communicationsmentioning
confidence: 99%
“…6 Shannon's polarizability table provides a method for identifying compositions that should have high dielectric constants. Because combinatorial synthesis is unlikely to be easily applicable to high-pressure experiments >1 GPa, theapproach we describe here requires some predictive modeling to increase the success rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The metastable form of BaLaMn 2 O 6 has already been mentioned. Another example is the partial ordering of Nd 3+ and Ag + , observed in NdAgTi 2 O 6 samples prepared under high-pressure conditions [22]. In 1984 Sekiya et al published the structure of NaLaMgWO 6 [24].…”
Section: Introductionmentioning
confidence: 99%
“…3 Park et al reported on the synthesis and structure of several new stoichiometric A-site systems. 4,5 Asite order-disorder reaction can play a critical role in affecting the properties of perovskites. Several studies have focused on the ionically conducting perovskites (RE 2/3−x Li 3x )TiO 3 (RE: rare earth).…”
Section: Introductionmentioning
confidence: 99%